2021
DOI: 10.1101/2021.02.04.429453
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolution and connectivity influence the persistence and recovery of coral reefs under climate change in the Caribbean, Southwest Pacific, and Coral Triangle

Abstract: Corals are experiencing unprecedented decline from climate change-induced mass bleaching events. Dispersal not only contributes to coral reef persistence through demographic rescue but can also hinder or facilitate evolutionary adaptation. Locations of reefs that are likely to survive future warming therefore remain largely unknown, particularly within the context of both ecological and evolutionary processes across complex seascapes that differ in temperature range, strength of connectivity, network size, and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 91 publications
(119 reference statements)
0
2
0
Order By: Relevance
“…Bay et al (2018) modeled adding 1-5% heat resistant corals to a cool-adapted population in the Cook Islands and found that this could help prevent population extinction in some future CO 2 emissions scenarios. However, this model of selection and others (e.g., Walsworth et al 2019, McManus et al 2021 do not take into account the growth tradeoff we see here.…”
Section: Resilience Tests In Conservation and Restorationmentioning
confidence: 73%
See 1 more Smart Citation
“…Bay et al (2018) modeled adding 1-5% heat resistant corals to a cool-adapted population in the Cook Islands and found that this could help prevent population extinction in some future CO 2 emissions scenarios. However, this model of selection and others (e.g., Walsworth et al 2019, McManus et al 2021 do not take into account the growth tradeoff we see here.…”
Section: Resilience Tests In Conservation and Restorationmentioning
confidence: 73%
“…The practical importance of identifying populations that are locally adapted to climate stress is rooted in the possibility that populations already harboring stress tolerant individuals might be used in restoration projects or in assisted evolution efforts to enhance the resilience of vulnerable populations (Aitken and Whitlock 2013;Mascia & Mills 2017;Seddon et al 2014). Norberg et al (2012), Walsworth et al (2019) and McManus et al (2021) used eco-evolutionary models to show that evolutionary responses to climate change stress could lead to higher levels of stable persistence than ecological models without evolution. Identifying source populations with such phenotypic variance could become especially critical for foundation species such as corals, forest trees, grasslands, and seagrasses (Franks et al 2014;Hodgins andMoore 2016, Morikawa and.…”
Section: Introductionmentioning
confidence: 99%